Flipped Classroom: Shifting from Conventional Approach to Innovative Model - Zainul Aminin; Much. Koiri (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study aims to deliver a detailed account of the prevailing literature while offering significant observations by accentuating the primary aspects of the flipped classroom and its benefits, factoring in the hurdles related to this teaching technique. The modern world is transforming into an environment where a wide range of technologies emerges, undergoes testing, and subsequently spreads swiftly. This significant transformation is evident in various fields, especially in education. This shift calls attention to the essential task of rethinking and rigorously scrutinizing the prevailing educational paradigm, the positions of instructors and students, and the teaching resources in practice. Additionally, the transition from traditional methods to innovative strategies is inevitable. The flipped classroom blends engaging learning experiences through collaborative and individual tasks in class, while lower-level tasks and self-study occur outside using digital resources. The researchers perform a theoretical review to thoroughly explore the incorporation of the flipped classroom model into our educational practices. The flipped classroom framework presents a promising strategy for boosting student learning and engagement. By thoughtfully addressing the related challenges and capitalizing on the potential advantages, educators can cultivate a more vibrant and effective learning atmosphere. Additional studies are required to evaluate the enduring consequences of the flipped classroom approach and to ascertain effective methods for its application.